Great ideas of man teachers guide - Jennings, Jerry E.; Prescott, Carol S.; Smith, Marion H. (Grand Rapids Fideler, 1970)
Describes concepts, or "ideas", such as government, language, education, and tools that have enabled men to live together in communities.
Keywords: Civilization -- History